Phytochemical Screening of Coconut Pistil Extract (Pistillum Cocos nucifera) as Traditional Medicine - Cukri Rahma; Mardi Fadillah; Nasrianti Syam; Rinawati Rinawati (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS (JPBN), 2024)
The coconut plant is a plant that has many benefits for human life. Every part of the coconut plant has great benefits for life, such as the trunk, roots, fruit, even the fruit or pistil of the coconut also provides many health benefits. Villagers use coconut pistil as a traditional medicine in the treatment of diarrhea. Traditional medicine can be obtained from plants that contain secondary metabolite compounds. Secondary metabolite compounds are active compounds found in plants to defend themselves from harmful environmental attacks. The purpose of this study is to identify secondary metabolite compounds present in coconut pistils. Identification of secondary metabolite compounds is carried out qualitatively, namely conducting phytochemical tests (phytochemical screening) in the laboratory. Phytochemical Screening is a simple and effective method. The results of this study indicate that coconut pistil (pistillum Cocos Nucifera) positively contains secondary metabolite compounds of flavonoids, saponins, tannins, terpenoids and phenolics. So that coconut pistil can be used as one of the traditional medicinal ingredients